On-site Determination of Lithium in Hot Spring Water by Portable Li-K Analyzer - Xiao LIU; Xiuchun ZHAN (Yankuang ceshi)
Lithium is an ideal material for green energy and lightweight alloys, and has been valued by many countries as an important strategic resource. Many hot springs, are rich in Li. However, hot springs are mainly distributed in remote areas such as Xizang and Yunnan, where the cost of sample transportation and laboratory testing is high and the efficiency is low, so the exploration of lithium resources urgently needs the support of on-site analysis technology. Hot spring water generally contains high concentrations of sodium, potassium and other elements, and the matrix effect is significant. In this study, the wavelength of the characteristic Li spectral line was set at 670.78nm. The analytical method for on-site determination of Li in hot spring water samples was established by a self-developed portable Li-K analyzer with a negative filter using the standard curve and standard addition methods. The experimental results show that when the electrolyte is 1.5% hydrochloric acid, the working current is 70mA and the sample flow rate is 3.0mL/min, the detection limit of Li is 4.07μg/L, and the measured precision (RSD) is better than 2%. The hot spring water samples were tested by standard addition, and the spiked recoveries were 81.6% to 115.9%. When the matrix composition of hot spring water samples is simple, accurate analysis results can be obtained by directly using the standard curve method. When the matrix composition of the sample is complex or the matrix concentration is high, the matrix effect can be effectively reduced by the standard addition method, and the analysis results obtained are relatively more accurate, which is suitable for the analysis of lithium content in hot spring water with different matrix types.